Application of nano zero-valent iron particles for the removal of phosphate from river water - Danila, Vaidotas; Januševičius, Tomas (International Conference “Environmental Engineering”, 2023)
Nano zero-valent iron (nZVI) particles have attracted much attention due to their ability to eliminate phosphate (PO4-P) from water. In this study, samples of river water with a high concentration of PO4-P were collected from Laukupė River, near the treated municipal wastewater drain outlet. The concentration of PO4-P in the sampled river water was 1.1 mg/L (bad ecological status). Adsorption experiments were carried out to determine the suitability of nZVI to remove PO4-P from actual river water. The applied dose of nZVI ranged from 0.05 g/L to 3.2 g/L, and contact time ranged from 5 to 120 min. The results have shown that the 0.4 g/L dose of nZVI was sufficient to reduce the PO4-P concentration below 0.05 mg/L after 5 min of contact time to reach a high ecological status of river water with respect to phosphate.